Potential Triggers of Lichen Planus: A Review - E.P. Sridevi Anjuga1 , N. Aravindha Babu2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Oral lichen planus (OLP) is mucocutaneous and chronic infl ammatory disease of unclear pathogenesis. OLPusually affects the mucous membrane of oral cavity. It is an autoimmune disorder araising from severaletiological factors like genetics, stress, virus, dental restorative materials, drugs and systemic diseases. It isa T-cell mediated autoimmune disease usually encountered by dentists and dermatologists. Although muchwork is being done on this disorder, there is still uncertainty over the specifi c etiopathogenesis and treatment.Because there is a risk of reported malignant potential with this disease, the patient needs early diagnosis andproper management. This article reviews mainly the etiology, pathogenetic mechanisms through which thisunique disorder occurs along with the aspects of clinical, histopathological and treatment.